The Influence of Business Capital, Product Innovation, and Business Training on MSMEs Performance in Pontianak - Alvincia, Velissa; Noviansius (Technology, Business and Entrepreneurship, 2024)
Micro, Small and Medium Enterprises (MSMEs) contribute significantly to Gross Domestic Product (GDP) and economic growth, despite facing challenges such as the pandemic and intensifying competition. This research aims to support MSMEs in Pontianak in improving performance through three main factors: venture capital, product innovation and business training. Adequate venture capital allows MSMEs to expand operations, expand markets and mitigate risks with an influence on MSME development of 62.5%. Product innovation, which includes new product development, quality improvement, and differentiation, influences MSME performance by 62.4%, while product development training provides knowledge and skills to produce better products and meet market needs. Using a quantitative approach through a survey of MSME owners or managers in Pontianak, this research ensures valid and reliable cross-sector representation, minimizes bias, and improves data accuracy.